The Influence of Financial Education and Financial Literacy on Savings Behavior with the Mediation of Financial Confidence - Andriani, Neneng Yanti; Syafii, Mochamad (Program Pascasarjana STIE Amkop Makassar, 2023)
This research explores the intricate relationships among financial education, financial literacy, financial confidence, and savings behavior within the context of Bank BRI KC Purwokerto. The study employs a quantitative approach, utilizing a sample of 40 individuals and applying the SmartPLS software for analysis. The direct test results reveal significant positive relationships between financial education and financial confidence, as well as between financial literacy and financial confidence. Financial confidence, in turn, significantly influences positive savings behavior. Additionally, the indirect test results highlight the mediating role of financial confidence in the relationship between financial education and savings behavior, as well as between financial literacy and savings behavior. These findings underscore the importance of not only imparting financial knowledge but also fostering financial confidence to promote positive savings behavior. The insights gleaned from this study have practical implications for policymakers, financial institutions, and educators seeking to enhance individuals' financial well-being and decision-making. Keywords: Financial Education, Financial Literacy, Savings Behavior, Financial Confidence